Proposing an inclusive model of travellers' visit intention and time perspective revisit intention - Chaichi, Kamelia *; Leong, Mei Kei *; Phongpanichanan, C; Nezakati, Hossein *; Hairani, M. N. & * (Society of Psychology and Education, 2021)
The tourism industry is one of the most crucial contributors to the economy of Malaysia. The antecedent of travellers’ behaviour and the various reasons for their visit and revisit intention is one of the significant factors that would help marketers to attract more tourists and maintain the sustainability of the industry. There is a lack of a comprehensive model to discuss various aspects of tourist visit intention and time perspective revisit intention, which was also rarely explored in previous literature. The current research is a concept nature study that attempts to fill this gap by proposing a complete comprehensive model of visit intention to predict the underlying reasons affecting travellers’ intention to visit. Based on this review, the following main aspects were recognized to impact travellers’ intention to visit which includes the “information source”, “travel constraints”, “destination image”, “traveller motivation”, “traveller experience”, and “risk perception”. The current paper aims to contribute to the sustainable tourism literature by providing a wide-ranging insight on traveller’s visit and time perspective revisit intention and could act as a point of reference for future studies on sustainable tourism development in Asian countries.